2010
DOI: 10.5304/jafscd.2010.012.008
|View full text |Cite
|
Sign up to set email alerts
|

Could Toronto provide 10% of its fresh vegetable requirements from within its own boundaries? Matching consumption requirements with growing spaces

Abstract: Is it feasible for Toronto to produce and market 10% of its fresh vegetable requirements from within its own boundary, without competing with existing Ontario vegetable producers? We used zoning maps, aerial photography, and numerous exclusionary and inclusionary criteria to identify potential food production sites across the city and, after identifying organic vegetable production yields, to calibrate supply potentials against current vegetable consumption estimates for the Toronto population. It was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 7 publications
(13 reference statements)
2
52
0
2
Order By: Relevance
“…From these data we computed the following linear relationship between building area per square meter and population per square meter (n = 2856 pixels, R 2 = 0.678): (Carter & Keeler, 2008). MacRae et al (2010) report that 37% of roofs in Toronto, Canada are "suitable for greening of some form." Here we adopt a conservative 19% suitability of estimated rooftop area for UA (i.e., the lowest value retrieved from the peer-reviewed literature).…”
Section: Vacant Landmentioning
confidence: 99%
“…From these data we computed the following linear relationship between building area per square meter and population per square meter (n = 2856 pixels, R 2 = 0.678): (Carter & Keeler, 2008). MacRae et al (2010) report that 37% of roofs in Toronto, Canada are "suitable for greening of some form." Here we adopt a conservative 19% suitability of estimated rooftop area for UA (i.e., the lowest value retrieved from the peer-reviewed literature).…”
Section: Vacant Landmentioning
confidence: 99%
“…Similarly, studies investigating the potential contribution of gardens to urban food supply are based either on production data obtained in different soil and climate contexts than their field of study, or on theoretical yields calculated from yields obtained in conventional agriculture (Darrot & Boudes, 2011;Grewal & Grewal, 2012;MacRae et al, 2010;McClintock et al, 2013). Yet it appears that the cropping practices of urban gardeners and the yields achieved in CGs differ significantly from what is observed in conventional agriculture (Algert et al, 2014).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…During the last decade, driven by the increasing popularity of CGs, several studies assessed the potential of CGs to contribute to the urban food supply (Darrot & Boudes, 2011;Grewal & Grewal, 2012;MacRae, Gallant, Patel, Michalak, Bunch & Schaffner, 2010;McClintock, Cooper, & Khandeshi, 2013). These studies concluded that a substantial part of urban food demand could be produced within the cities' own boundaries by putting vacant land into production.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…As evidence of this potential, recently at least three farming operations in Toronto led by young farm entrepreneurs have started CSAs using backyard production. Two research papers were recently published in the Journal of Agriculture, Food Systems, and Community Development on scaling up urban agriculture in Toronto (MacRae, Gallant, Patel, Michalak, Bunch, & Schaffner, 2010;MacRae et al, 2012). The MacRae et al (2010) study examined the potential for vegetable production on land located within the city of Toronto.…”
Section: Introductionmentioning
confidence: 99%
“…Two research papers were recently published in the Journal of Agriculture, Food Systems, and Community Development on scaling up urban agriculture in Toronto (MacRae, Gallant, Patel, Michalak, Bunch, & Schaffner, 2010;MacRae et al, 2012). The MacRae et al (2010) study examined the potential for vegetable production on land located within the city of Toronto. This study brings together the two arenas of urban agriculture and community supported agriculture, examining urban CSA possibilities in Toronto through more in-depth analysis of the land parcels identified in the MacRae et al (2010) paper.…”
Section: Introductionmentioning
confidence: 99%